2016
DOI: 10.1016/j.funbio.2016.07.012
|View full text |Cite
|
Sign up to set email alerts
|

Detection of N2O-producing fungi in environment using nitrite reductase gene (nirK)-targeting primers

Abstract: Fungal denitrification has been increasingly investigated, but its community ecology is poorly understood due to the lack of culture-independent tools. In this work, four pairs of nirK-targeting primers were designed and evaluated for primer specificity and efficiency using thirty NO-producing fungal cultures and an agricultural soil. All primers amplified nirK from fungi and soil, but their efficiency and specificity were different. A primer set, FnirK_F3/R2 amplified ∼80 % of tested fungi, including Aspergil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 47 publications
1
24
0
Order By: Relevance
“…Similar genera were also observed in phase I and phase II, including unclassified Rhodobacteraceae , Amaricoccus and unclassified Comamonadaceae . Many frequently detected members of families Rhodobacteraceae and Comamonadaceae had the function of denitrification . Operating at the same DR, the microbial community in phase IV with less DO had higher similarity with that in phase II.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…Similar genera were also observed in phase I and phase II, including unclassified Rhodobacteraceae , Amaricoccus and unclassified Comamonadaceae . Many frequently detected members of families Rhodobacteraceae and Comamonadaceae had the function of denitrification . Operating at the same DR, the microbial community in phase IV with less DO had higher similarity with that in phase II.…”
Section: Resultsmentioning
confidence: 95%
“…It was shown that unclassified Rhodocyclaceae ( Rhodocyclaceae family) was the largest genus in phase I and phase III with the DR of 0.23, while Pseudomonas genus was the largest genus in phase II and phase IV with the DR of 0.14. Rhodocyclaceae were one of the families most frequently reported to be related with denitrification, including Azoarcus , Dechloromonas , Thauera and Zoogloea , etc . The Pseudomonas genus from Pseudomonasaceae family also plays an important role in nitrogen removal in normal or salt/marine environment .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several primers have been designed for fungal nirK recently (Long et al, 2015;Maeda et al, 2015;Wei et al, 2015a;Chen et al, 2016;Novinscak et al, 2016). Two fungal denitrification genes have been targeted for development of molecular methods: nirK and P450nor.…”
Section: Bmentioning
confidence: 99%
“…These primers were tested here for coverage against 159 available fungal nirK sequences from a variety of taxonomy groups (Table 1 and Supporting Information Table S7). When these primers were tested by amplifying soil DNA and constructing clone libraries, the resulting sequence analysis indicated that all the primer sets for fungal nirK had nonspecific amplification of bacterial nirK sequences, although to different extents (Chen et al, 2016). Due to the high similarity of bacterial and fungal nirK sequences, the fungal nirK primers were also tested for specificity against the 361 bacterial and archaeal nirK sequences used for testing bacterial nirK primers.…”
Section: Bmentioning
confidence: 99%